Utilization of Bamboo Materials as Building Construction Envi-ronmentally Friendly and Positive for Nature (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Previous studies have shown that the use of bamboo in building construction, which has a significant impact on the earth and the future of humanity, such as reducing the carbon footprint in construction waste. However, there is still potential for further development in optimizing the use of bamboo from various aspects of building construction. This study aims to continue previous research by focusing on efforts to improve the efficiency and effectiveness of bamboo use, while also expanding our understanding of its positive impacts on the environment. The research method used involves an in-depth literature review to understand the latest developments in technology and practices of bamboo use in building construction. In addition, conducting data analysis from various construction projects that have used bamboo as the main material or structural component. This analysis aims to identify patterns of success and obstacles faced in the application of bamboo in different construction contexts. To validate these findings, a series of field trials were also conducted to test the practical application of the proposed strategies and techniques. These field trials were conducted by several studies at various construction sites representing diverse geographic and climatic conditions. The data collected from these field trials provide valuable insights into the performance of bamboo in real-world situations, as well as providing direct input from relevant stakeholders